PENGUJIAN VARIABEL DER DAN VARIABEL CR TERHADAP VARIABEL ROE DALAM MENGHASILKAN LABA SUB SEKTOR TELEKOMUNIKASI DI BEI - Trie Sartika Pratiwi (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
Based on research that has been carried out on the effect of capital structure and liquidity on profitability which has been carried out through the variables of the Dept. Equity Ratio, Current Ratio, and Return On Equity, it can be concluded that the results of the F test indicate that capital structure and liquidity have a significant effect on profitability in sub-companies. telecommunications sector listed on the Indonesia Stock Exchange. The results of the t-test indicate that the capital structure has a significant negative effect on the profitability of the telecommunications sub-sector companies listed on the Indonesia Stock Exchange. The results of the t-test indicate that liquidity has a significant positive effect on profitability in the telecommunications sub-sector companies listed on the Indonesia Stock Exchange.Keywords: DER variable, CR variable, ROE variable